EVALUATION OF THE PRESENCE OF POLYMORPHIC FORMS AND INFLUENCE ON THE DISSOLUTION PROFILE OF TENOXICAM IN ACTIVE PHARMACEUTICAL INGREDIENT AND FORMULATIONS - Aline Taís Fries; Natália Olegário; Sarah Chagas Campanharo; Vitor Paulo Pereira; Martin Steppe (Drug Analytical Research, 2018)
Polymorphism is a relatively common phenomenon among pharmaceutical compounds, and one of the main aspects to be considered in the production and development of medications. The investigation of polymorphism associated with oxicams, a group belonging to the class of non-steroidal anti-inflammatory drugs (NSAIDs) has increased in recent years and, in the case of tenoxicam, the existence of four polymorphic forms is reported in the literature. The objective of this study was to characterize the presence of different polymorphic forms of tenoxicam in active pharmaceutical ingredient and oral pharmaceutical formulations, as well as to evaluate the influence on in vitro dissolution. The characterization of the three samples of pharmaceutical ingredient of tenoxicam from different suppliers by X-Ray Diffraction (XRD), Infrared (IR) and dissolution profile indicated the presence of a form III crystalline structure, without presenting significant differences between the in vitro dissolution profiles analyzed, and a Dissolution Efficiency (DE%) of 60.30%, 60.70% and 72.34%, respectively. When the four pharmaceutical specialties of tenoxicam were submitted to XRD analysis, they also presented form III crystalline structures. Despite this, the formulations presented different dissolution profiles and a DE% of 75.23%, 83.69%, 78.19% and 90.63%, respectively, without compromising their quality. However, often polymorphism affects physico-chemical properties of drugs, showing the importance of studying this phenomenon, by correlating the presence of crystalline structures to alterations in the quality of active ingredients and pharmaceutical products.